A novel wideband perforated dielectric reflectarray. Issue 12 (29th July 2019) - Xi, Baokun; Xue, Qianzhong; Cai, Yang; Wang, Yong; Yang, Shaopeng; Zhang, Rui
Abstract: This work proposes a new methodology for widening the bandwidth of a reflectarray (RA) antenna. The narrow impedance of the conventional dielectric RA can be effectively widened on the basis of the gradual impedance matching principle. A multilayer element can realize impedance matching to free space by suitably choosing the different diameters in different layers of the drilled air‐vias. Besides, a series of air‐vias with varying diameters changes the resonance frequencies and partially overlapped bandwidth between one another, which results in widening the bandwidth. To validate the wideband RA antenna design, a circular RA prototype with diameter of 96 mm is simulated, fabricated, and measured. The measured RA exhibits an improved 1‐dB gain bandwidth of 18.4%. A peak gain of 25.18 dBi with maximum aperture efficiency of 52.18% is obtained. The significant experimental performance improvement confirms that bandwidth can be efficiently broadened by introducing the tapered scheme.